Напрями активізації освітньо-прикладного проектування на кафедрі дизайну архітектурного середовища львівської архітектурної школи тепер і в майбутньому - Проскуряков, В. І.; Лопоша, М. А.; Кубай, Н. Р.; Гречка, У. М.; Proskuryakov, V. I.; Loposha, M.; Kubay, N. R.; Grechka, U. M. (Видавництво Львівської політехніки, 2018)
У ХХІ ст. в Україні актуальна тема освіти і науки, її теперішнього стану і майбутнього. Сьогодні сформувалося чотири типи, на які орієнтуються і освіта в Україні, й архітектурна зокрема, хоча, на відміну від європейської освіти, національна українська освіта ще й досі орієнтується на «середньостатистичного», «типового» студента.

The main difference between education in Ukraine and abroad lies in the fact that abroad 1st years students as well as 5th year students can work on any project having chosen their mentor independently. Having examined and compared studying methods at Ukrainian universities and the university of Hanover, universities in Canada, Manchester school of architecture it has been discovered that foreign students from the beginning of studies have scientific and designing seminars, cooperate closely with architecture companies, have a lot of programs for gaining practical skills. At English architecture schools they have one year for gaining practical experience of an architect-professional. While studying education activity of Ukrainian architecture schools (there are 16 of them in 12 cities of Ukraine) it can be noticed that all of them widely cultivate only one basic type, for instance the architecture faculty of the National academy of visual arts and architecture where artistic workshops have become popular and are managed by famous pedagogues-architects. Nonetheless, university type dominates at architecture schools of Kyiv National University of Construction and Architecture. Educationally-designing activity at all architecture schools of Ukraine, similar to education structure of the mentioned foreign ones, starts 1–2 years later. What is the reason for that? It is because during first two years all architecture schools without exception, should additionally teach “fresh” architecture students classical architecturally-technical subjects, basic elements of which (drawing, sketching) are nowadays excluded from schools curriculum. It can influence the increase of level of educational processes at the first courses in Ukraine in current conditions syncretic integration of all education types into a single hereditary process from younger courses to the older ones. Taking into account previous educational potential of students – architects, monitoring studying progress. Making education directed, personalized, flexible.
Directions of activation of education-applied designing at the architectural media discovery department of the Lviv architectural school of the now and the future
Keywords: інтенсивність та прогрес; освітньо-проектна діяльність; каталізатори освітніхпроцесів; синкретична інтеграція історично сформованихтипів освіти; індивідуальний освітній потенціал студента; intensity and progress; educational and project activity; catalysts of educational processes; syncretic integration of historically formed types of education; individual educational potential of the student; 711.73